Nepal Energy Infrastructure Sector Assessment - World Bank Group (World Bank, Washington, DC, 2019)
The purpose of this report is to identify how to maximize finance available to Nepal in the electricity sector. This report identifies financing needs and constraints for the energy sector in the short to medium term and outlines a road map for overcoming these constraints and seizing opportunities to gradually achieve a sectoral transformation. The report forms part of the World Bank Group’s Infrastructure Sector Assessment Program (INFRA-SAP).